Beyond the classical thermodynamic contributions to hydrogen atom abstraction reactivity - Bím, Daniel; Maldonado-Domínguez, Mauricio; Rulíšek, Lubomír; Srnec, Martin (Proceedings of the National Academy of Sciences of the United States of America, 2018)
Hydrogen atom abstraction (HAA) reactions are cornerstones of chemistry. Various (metallo)enzymes performing the HAA catalysis evolved in nature and inspired the rational development of multiple synthetic catalysts. Still, the factors determining their catalytic efficiency are not fully understood. Herein, we define the simple thermodynamic factor η by employing two thermodynamic cycles: one for an oxidant (catalyst), along with its reduced, protonated, and hydrogenated form; and one for the substrate, along with its oxidized, deprotonated, and dehydrogenated form. It is demonstrated that η reflects the propensity of the substrate and catalyst for (a)synchronicity in concerted H+/e- transfers. As such, it significantly contributes to the activation energies of the HAA reactions, in addition to a classical thermodynamic (Bell-Evans-Polanyi) effect. In an attempt to understand the physicochemical interpretation of η, we discovered an elegant link between η and reorganization energy λ from Marcus theory. We discovered computationally that for a homologous set of HAA reactions, λ reaches its maximum for the lowest |η|, which then corresponds to the most synchronous HAA mechanism. This immediately implies that among HAA processes with the same reaction free energy, ΔG0, the highest barrier (≡ΔG≠) is expected for the most synchronous proton-coupled electron (i.e., hydrogen) transfer. As proof of concept, redox and acidobasic properties of nonheme FeIVO complexes are correlated with activation free energies for HAA from C-H and O-H bonds. We believe that the reported findings may represent a powerful concept in designing new HAA catalysts.
Keywords: hydrogen atom transfer; reduction potential; asynchronicity factor; acidity constant; reorganization energy